2007
DOI: 10.1111/j.1365-2222.2007.02806.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 levels in asthma: relation with disease severity and aspirin sensitivity

Abstract: This study indicated that diminished LX A4 generation was unique to severe asthma phenotype regardless of comorbid aspirin sensitivity. Clinical Implications Lower LX A4 levels in severe asthma would suggest a possibility for LX analogues as future treatment options in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 42 publications
(65 reference statements)
1
39
0
Order By: Relevance
“…Lipoxins are also formed in vivo and are associated with inflammatory events, as LXA 4 is present in BALF from patients with respiratory inflammation (29). Individuals with asthma possess the capacity to generate LXs, but activated whole blood from aspirin-intolerant subjects with asthma and subjects with severe asthma displays relative decrements in LXA 4 biosynthesis (24,30,31). In contrast to LXs, leukotriene levels (LTB 4 and CysLTs) are increased in activated whole blood from subjects with severe asthma compared with those with nonsevere asthma (24).…”
Section: Discussionmentioning
confidence: 99%
“…Lipoxins are also formed in vivo and are associated with inflammatory events, as LXA 4 is present in BALF from patients with respiratory inflammation (29). Individuals with asthma possess the capacity to generate LXs, but activated whole blood from aspirin-intolerant subjects with asthma and subjects with severe asthma displays relative decrements in LXA 4 biosynthesis (24,30,31). In contrast to LXs, leukotriene levels (LTB 4 and CysLTs) are increased in activated whole blood from subjects with severe asthma compared with those with nonsevere asthma (24).…”
Section: Discussionmentioning
confidence: 99%
“…Leukotriene receptor antagonists are widely used as another first-line therapeutic agent in asthma, suggesting that abnormal lipid metabolism contributes to disease pathophysiology. Recently, several reports have indicated that biosynthesis of anti-inflammatory and pro-resolving lipid mediators, lipoxin A4 (LXA4) or protectin D1 (PD1), are dysregulated in severe asthma (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), suggesting that an imbalance between pro-and anti-inflammatory molecules causes the exacerbation of inflammation observed in airways of asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…LXs play a key counterregulatory role in mouse models of infection with Mycobacterium tuberculosis and Toxoplasma gondii ( 1 -3, 7 ). Similarly, defi cient LX-mediated counterregulation has been linked to the pathogenesis of infl ammatory diseases, such as severe asthma ( 8 ), cystic fi brosis lung disease ( 3 ), and periodontal disease ( 7 ). The benefi cial eff ects of LX analogue administration in diverse rodent models of infl ammatory pathology, along with the observation that administration of the widely used antiinfl ammatory drug ASA leads to the generation of metabolically more stable LX carbon 15-epimers (ASA-triggered LX [ATL]), has suggested therapeutic promise for specifi c harnessing of the biological activities of these potent lipid mediators.…”
mentioning
confidence: 99%